The Heart Is As Important As the Mind for Higher Education Renewal - Megan A. Scanlon (The University of Alabama, 2022)
Review of the book: Parker J. Palmer and Arthur Zajonc, The Heart of Higher Education: A Call to Renewal. San Francisco, California: Jossey-Bass, 2010. 256 pages. ISBN: 978-0-470-48790-7